A Systematic Review on Effect of Canagliflozin in Special Population - Patel, Sanket; Gohel, Kalpesh; Gordhanbhai Patel, Bharat (Current Diabetes Reviews, 2016)
Canagliflozin is a competitive, reversible, highly selective SGLT2 inhibitor and available in 100mg and 300mg as oral tablet form. Owing to this, it induced glucosuria and cause changes in glucose homeostasis without affecting insulin. This review addressed the efficacy and safety of canagliflozin in a specialized patients such as chronic kidney disease (stage III CKD), high risk cardiovascular patient and elderly population. Canagliflozin has reduced HbA1c in all the specialized population, albeit reduction is less as compared to the normal cohort. Additionally, canagliflozin causes reduction in body weight as well as in blood pressure. It was very well tolerated and did not produce significant adverse events compared to standard care (placebo) except genital mycotic infection due to glucosuria. In cardio vascular safety analysis, canagliflozin might be associated with increased incidence of major adverse cardiovascular plus (MACE plus) events in the initial period, which is of concern in a high- risk cardiovascular cohort. In patients with type 2 diabetes mellitus (T2 DM) and stage III CKD cohort, canagliflozin was well tolerated without much affecting eGFR and should be initiated with 100mg. Canagliflozin showed good safety profile in elderly population with T2DM without significantly affecting overall bone mineral density and bone resorption.
Keywords: resorption